The Analysis of Supply Chain Management System Needs in Sales Transaction Business of PT Digital Satu Media Indonesia - Reonaldy Berikang; Yuliana Mose; Dedi Sorongan (Budapest International Research and Critics University, 2022)
The planning process for building a system is very important because it is the architecture and the basis for building an information system. How an information system can run effectively and efficiently in it must have a business strategy for the distribution process that must be thought out carefully and follow a structured process to achieve success. Supply Chain Management has the right formula to do just that. The processes in Supply Chain Management are needed in the business processes run by PT Digital Media Satu Indonesia, in this case as a service provider for selling vegetable products which are supplied directly from the agricultural center in North Sulawesi, namely Modoinding District. Company policies and rules can be adopted from the existing concepts in the MRP. The planned system will be analyzed at an early stage, as well as an analysis of how the data flow will work on the system in question. In addition to carrying out systematic digital sales activities, this concept will also help farmers to get clearer directions and goals for their harvests, especially for regular consumers, which will automatically make these business activities and processes better and more perfect.This research was carried out using descriptive research methods, which will produce a product that runs the MRP concept in it.